The role of socio-economic and cultural factors in municipal solid waste generation: a case study in Taman Perling, Johor Bahru - Mohd.Yusof, Mohd. Badruddin; Othman, Fadil; Hashim, Normala; Ali, Nur Cahaya (Penerbit UTM Press, 2002)
The absence of a comprehensive database on solid waste generation and composition appears to be the major drawback to the development of an integrated waste management system in Malaysia. While many studies have been conducted on related fields, such as Abd. Karim et al. (1996), Sabarinah (1997), and Salim et al. (1994), there is still a lack of clear model or approach in determining attributes influencing the amount of wastes generated by our community. A study conducted in Taman Perling, Johor Bahru has shown that such as attributes as income, education, and other socioeconomic factors barely affect the amount of waste generated. It seems that only family size and lifestyle factors, particularly the eating habits of residents, contribute significantly to variations in the generation of residential waste in the study area. While the amount increases with the size of family, it decreases as the respondents dine out more often. This study suggests new insights concerning the role of social factors and lifestyle in affecting the generation of household waste.